Achieving 19% Power Conversion Efficiency in Planar‐Mixed Heterojunction Organic Solar Cells Using a Pseudosymmetric Electron Acceptor. Issue 32 (11th July 2022) - Gao, Wei; Qi, Feng; Peng, Zhengxing; Lin, Francis R.; Jiang, Kui; Zhong, Cheng; Kaminsky, Werner; Guan, Zhiqiang; Lee, Chun‐Sing; Marks, Tobin J.; Ade, Harald; Jen, Alex K.‐Y.
Abstract: A record power conversion efficiency (PCE) of over 19% is realized in planar‐mixed heterojunction (PMHJ) organic solar cells (OSCs) by adopting the asymmetric selenium substitution strategy in making a pseudosymmetric electron acceptor, BS3TSe‐4F. The combined molecular asymmetry with more polarizable selenium substitution increases the dielectric constant of the D18/BS3TSe‐4F blend, helping lower the exciton binding energy. On the other hand, dimer packing in BS3TSe‐4F is facilitated to enable free charge generation, helping more efficient exciton dissociation and lowering the radiative recombination loss (Δ E 2 ) of OSCs. As a result, PMHJ OSCs based on D18/BS3TSe‐4F achieve a PCE of 18.48%. By incorporating another mid‐bandgap acceptor Y6‐O into D18/BS3TSe‐4F to form a ternary PMHJ, a higher open‐circuit voltage ( V OC ) can be achieved to realize an impressive PCE of 19.03%. The findings of using pseudosymmetric electron acceptors in enhancing device efficiency provides an effective way to develop highly efficient acceptor materials for OSCs. Abstract : A pseudosymmetric electron acceptor, BS3TSe‐4F, designed from asymmetric selenium substitution strategy promotes free charge generation to enhance exciton dissociation and suppress energy loss in sequentially processed organic solar cells, leading to a record power conversion efficiency of over 19%.